Scars of War: The Legacy of WW1 Deaths on Civic Capital and Combat Motivation - Felipe Carozzi; Edward Pinchbeck; Luca Repetto (Center for Economic Studies and ifo Institute (CESifo), 2023)
How does the memory of lives lost in past wars shape communities and the next generation of soldiers? We use newly collected geolocated data on British servicemen to study the legacy of the Great War mortality shock on local communities and the behaviour of soldiers in WW2. We find that community-wide fatalities in WW1 increase the numbers of deaths of the next generation in WW2 and the likelihood that these soldiers receive military honours. To explain these findings, we report that WW1 deaths had promoted civic-oriented and cooperative behaviours in the inter-war period, as measured by the creation of lasting war memorials, veterans' associations and charities, and increases in voter participation. Overall, we present evidence that part of the legacy of the Great War on British servicemen runs through and is amplified by civic capital and the remembrance of fallen soldiers.
Keywords: D74; D91; O15; Z10; 330; World War; communities; combat motivation; conflict